(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The stress among teachers may effects their performance and their belief about themselves. So, the need was felt to conduct research on the phenomenon of stress management. The study of stress management among teachers is of great significance. One’s abilities are reflected through the performance and that performance is directly related to the mental state and physique. The school place where future nation is shaped. In the present study, the attempt is to highlight the level of stress management among secondary school teachers talking in to consideration their gender and locality difference. The different of school teacher’s help with helps us know the difference in the level of stress management if it exists. In this paper significant differences if any between two groups of secondary school teachers of different locality (urban and rural) in reference to their stress management, compare the two group of secondary school teachers of different gender (male and female) in reference to their stress management.